(untitled) (Jurnal kesehatan komunitas (Journal of community health), 2025)
The negative stigma towards PLWHA held by health workers makes people reluctant to take an HIV test because they are afraid of positive results and are worried about getting discriminatory services in primary health care. Stigma towards PLWHA occurs due to lack of knowledge about safe working methods in handling HIV/AIDS, homophobic attitudes, and religiosity. This study aims to describe the stigma and its determinants in health workers in Balikpapan City. The study design was cross-sectional. The population was health workers working in primary health care in Balikpapan City including general practitioners, nurses, midwives, pharmacists and laboratory staff. The population was 4284 people spread across 27 Health Centers in Balikpapan. The sampling type was quota sampling, calculated using the Lemeshow formula to obtain a sample size of 423. The instrument used to measure stigma was the Health Care Providers HIV/AIDS Stigma Scale (HPASS). Data analyzed using bivariat analysis. The results showed that most health workers still had a stigma towards PLWHA (53%). Individuals with the greatest high stigma were individuals who had never received HIV training (59.7%). Bivariate analysis showed that there was a relationship between stigma and HIV training (pvalue = 0.026). Regular training is needed on handling and assisting HIV/AIDS patients for health workers in Primary Health Care, in order to controlled the stigma.